Kualitas Audit Sebagai Variabel Pemoderasi Antara Key Audit Matters (KAM) dan Audit Report Lag - Pruenta Azzalea Adjani; Marita Marita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of KAM disclosure on audit report lag with audit quality as a moderating variable. This study was conducted on Energy Sector Companies listed on the Indonesia Stock Exchange (IDX) in 2023-2024. This is a descriptive quantitative study using purposive sampling with a sample size of 60 companies. The analysis technique used is Moderated Regression Analysis (MRA) using SPSS version 27.0. The results of this study are: 1) KAM disclosure does not have a significant positive effect on audit report lag; 2) Audit quality has a significant negative effect on audit report lag; 3) Audit quality successfully moderates the effect of KAM disclosure on audit report lag.